Vandetanib in Children and Adolescents with Multiple Endocrine Neoplasia Type 2B Associated Medullary Thyroid Carcinoma - Fox, Elizabeth; Widemann, Brigitte C.; Chuk, Meredith K.; Marcus, Leigh; Aikin, Alberta; Whitcomb, Patricia O.; Merino, Maria J.; Lodish, Maya; Dombi, Eva; Steinberg, Seth M.; Wells, Samuel A.; Balis, Frank M. (Clinical cancer research, 2013)
Purpose: Medullary thyroid carcinoma (MTC) is a manifestation of multiple endocrine neoplasia type 2 (MEN2) syndromes caused by germline, activating mutations in the RET (REarranged during Transfection) proto-oncogene. Vandetanib, a VEGF and EGF receptor inhibitor, blocks RET tyrosine kinase activity and is active in adults with hereditary MTC. Experimental Design: We conducted a phase I/II trial of vandetanib for children (5–12 years) and adolescents (13–18 years) with MTC to define a recommended dose and assess antitumor activity. The starting dose was 100 mg/m2 administered orally, once daily, continuously for 28-day treatment cycles. The dose could be escalated to 150 mg/m2/d after two cycles. Radiographic response to vandetanib was quantified using RECIST (v1.0), biomarker response was measured by comparing posttreatment serum calcitonin and carcinoembryonic antigen (CEA) levels to baseline, and a patient-reported outcome was used to assess clinical benefit. Results: Sixteen patients with locally advanced or metastatic MTC received vandetanib for a median (range) 27 (2–52) cycles. Eleven patients remain on protocol therapy. Diarrhea was the primary dose-limiting toxicity. In subjects with M918T RET germline mutations (n = 15) the confirmed objective partial response rate was 47% (exact 95% confidence intervals, 21%–75%). Biomarker partial response was confirmed for calcitonin in 12 subjects and for CEA in 8 subjects. Conclusion: Using an innovative trial design and selecting patients based on target gene expression, we conclude that vandetanib 100 mg/m2/d is a well-tolerated and highly active new treatment for children and adolescents with MEN2B and locally advanced or metastatic MTC. Clin Cancer Res; 19(15); 4239–48. ©2013 AACR.